2008
DOI: 10.1007/s10561-008-9105-0
|View full text |Cite
|
Sign up to set email alerts
|

Fresh cortical autograft versus fresh cortical allograft effects on experimental bone healing in rabbits: radiological, Histopathological and Biomechanical evaluation

Abstract: Bone grafting is used to enhance healing in osteotomies, arthrodesis, and multifragmentary fractures and to replace bony loss resulting from neoplasia or cysts. They are source of osteoprogenitor cells and induce bone formation and provide mechanical support for vascular and bone ingrowth. Autografts are used commonly but quantity of harvested bone is limit. This study was designed to evaluate fresh cortical autograft and allograft effects on bone healing process. Twenty male White New Zealand rabbits were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 25 publications
0
38
0
1
Order By: Relevance
“…Clinical data obtained during long-term follow-up indicated that allograft surgical procedures were equivalent or superior to autograft transplantation (Shafiei et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Clinical data obtained during long-term follow-up indicated that allograft surgical procedures were equivalent or superior to autograft transplantation (Shafiei et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…For example, the amount of donor tissue available and complications at the donor site are limiting factors for autogenous bone grafting. In the case of allogeneic bone grafts, cell-mediated immune responses and pathogen transfer can be problematic [6]. Besides, metal materials, inorganic nonmetallic materials and organic materials have been used for bone repair with the development of medicine, biology and materials science.…”
Section: Introductionmentioning
confidence: 99%
“…Bone healing is not sufficient in large bone defects and may be complicated. Under these circumstances, the autografts are the most popular method for bone replacement [4][5][6]. In some instances, autografts cannot be used for filling such large defects.…”
Section: Introductionmentioning
confidence: 99%